1991
DOI: 10.1128/aac.35.9.1914
|View full text |Cite
|
Sign up to set email alerts
|

Activity of pentamidine and pentamidine analogs against Toxoplasma gondii in cell cultures

Abstract: The capabilities of pentamidine and nine pentamidine analogs to inhibit the development of Toxoplasma gondii were examined in vitro. Treatment of infected cultures with pentamidine and five of its analogs caused a significant (P less than 0.05) reduction in the numbers of tachyzoites produced. Analogs of pentamidine may be useful agents in the treatment of toxoplasmosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 19 publications
0
20
1
1
Order By: Relevance
“…In that study, pentamidine at 25 and 10µg/mL was shown to have significant effects over tachyzoite replication. Lindsay et al 17 obtained a different result from that in the present work, where no anti-Toxoplasma activity of pentamidine was observed at tested concentrations. The conflicting results between these studies may be due to the different cell lines used or differences in methodology because there is no standard model among the authors who perform assays with drugs 17 .…”
Section: Acknowledgmentscontrasting
confidence: 90%
See 1 more Smart Citation
“…In that study, pentamidine at 25 and 10µg/mL was shown to have significant effects over tachyzoite replication. Lindsay et al 17 obtained a different result from that in the present work, where no anti-Toxoplasma activity of pentamidine was observed at tested concentrations. The conflicting results between these studies may be due to the different cell lines used or differences in methodology because there is no standard model among the authors who perform assays with drugs 17 .…”
Section: Acknowledgmentscontrasting
confidence: 90%
“…More recent studies such as those by Dumas et al 15 and Soheilian et al 16 support the use of this combination to prevent cerebral and ocular toxoplasmosis [14][15][16] . Lindsay et al 17 examined the ability of pentamidine and nine of its analogs to inhibit the replication of RH strain T. gondii in Vero cell cultures. In that study, pentamidine at 25 and 10µg/mL was shown to have significant effects over tachyzoite replication.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Recent studies have found that a number of direct analogs of pentamidine have activity against Pneumocystis carinii (19), Giardia lamblia (3), Toxoplasma gondii (25), Cryptosporidium parvum (7), Leishmania amazonensis subsp. mexicana (5), and Plasmodium falciparum (5).…”
mentioning
confidence: 99%
“…[2] Lindsay et al [3] demonstrated the activity of pent-A C H T U N G T R E N N U N G amidine 1 against Toxoplasma gondii in in vitro studies. Furthermore, pentamidine 1 is established in the treatment of Pneumocystis pneumonia (PcP).…”
Section: Introductionmentioning
confidence: 99%